Clinical Outcome of Nerve Decompression Surgery for Migraine Improves with Nerve Wrap. Issue 10 (October 2021) - Alizadeh, Kaveh; Kreinces, Jason B.; Smiley, Abbas; Gachabayov, Mahir
Abstract : Background: Chronic migraine headaches affect nearly 30 million Americans every year and are responsible for roughly 1.2 million emergency department visits annually. Many of the standard therapies commonly used to treat migraines are often unsuccessful and may furthermore introduce unwanted side effects. The purpose of this study was to identify independent predictors of clinical improvement in patients undergoing surgical nerve decompression for migraine. Methods: A retrospective chart review between 2010 and 2020 was conducted. The primary endpoint was clinical improvement at 1-year follow-up, defined as an independence from prescription medications. Patients were stratified into two groups: clinical improvement and treatment failure. Backward multivariable logistic regression was used to examine the associations between migraine improvement and different patient characteristics. Results: A total of 153 patients were included. In total, 129 (84.3%) patients improved and 24 (15.7%) did not. Significant associations with clinical improvement at multivariable logistic regression were found with acellular dermal matrix nerve wrap (OR = 10.80, 95%CI: 6.18–16.27), and operation of trigger sites four (OR = 37.96, 95%CI: 2.16–73.10) and five (OR = 159, 95%CI: 10–299). Conclusion: The use of acellular dermal matrix nerve wraps in surgery was significantly associated with clinical migraine improvement, as was operation at trigger sites four and five.